2007
DOI: 10.1590/s1413-86702007000500007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for chronic hepatitis B in HIV patients attended at a sexually-transmitted disease clinic in Vitoria, Brazil

Abstract: This study assessed the prevalence of and correlated factors for chronic hepatitis B infection (HBV) among HIV patients attending the Reference Center for Sexually Transmitted Infections (STI) and AIDS in Vitória, ES, Brazil. HIV patients were studied from 1993 to 2004, using information recorded in a database of the STI Clinic. Demographic data, clinical characteristics, patterns of risk behavior and test results (ELISA-HIV, IFA-HIV, HBsAg, viral load and CD4 counts) were analyzed. We analyzed 851 HIV patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
2
13
1
2
Order By: Relevance
“…HBV/HIV and HCV/HIV prevalences were 3.7% and 5.4% respectively. These are in accordance with other Brazilian published data, in which values ranged from 2.8%-4.6% for HBV/HIV co-infection (7,15,19) and 4%-6.4% for HCV/HIV association (6,7,17) . Similar to our study, these researches tested HIV patients who were in medical follow-up in infectious disease centers in four distinct Brazilian cities: São Paulo, Porto Alegre, Amazonas and Vitória.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…HBV/HIV and HCV/HIV prevalences were 3.7% and 5.4% respectively. These are in accordance with other Brazilian published data, in which values ranged from 2.8%-4.6% for HBV/HIV co-infection (7,15,19) and 4%-6.4% for HCV/HIV association (6,7,17) . Similar to our study, these researches tested HIV patients who were in medical follow-up in infectious disease centers in four distinct Brazilian cities: São Paulo, Porto Alegre, Amazonas and Vitória.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies also reported a higher frequency of these co-infections among men and most of them describe the age interval of 35 -40 years as the most prevalent (11,15,17,19,20) . A considerable percentage of patients referred to have multiple sexual partner/year.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies of syphilis infection have found 1.2% of pregnant women have markers for latent infection, and up to 16.0% of female prisoners have these markers (Costa et al, 2007;Miranda et al 2000). Chronic HBV has been identified in 1.1% of women presenting for antenatal care (Miranda et al, 2001; Lima and Tanure, 2003), 5.4% of women attending an STI clinic (Miranda et al, 1999), 7.4% among female prisoners (Miranda et al, 2000) and 3.8% of female HIVinfected patients (Zago et al, 2007). Anti-HCV has been detected among 1.4% of pregnant women tested, and 19.0% of female prisoners (Lima, 2003;Miranda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among patients co-infected with the human immunodeficiency virus (HIV), HBV prevalence in Brazil varies from 1.6-8.5% (Mendes-Correa et al 2000, Monteiro et al 2004, Souza et al 2004, Tovo et al 2006, Zago et al 2007, Portelinha Filho et al 2009). HIV coinfection modifies hepatitis B progression by decreasing the anti-HBV immune response after acute HBV infection, thereby increasing the risk of chronic infection (Benhamou 2007).…”
mentioning
confidence: 99%